Low-level aerial photogrammetry as a source of supplementary data for ALS measurements - Bobkowska, Katarzyna; Inglot, Adam; Przyborski, Marek; Sieniakowski, Jędrzej; Tysiąc, Paweł (International Conference “Environmental Engineering”, 2017)
The development of laser scanning technology ALS allows to make high-resolution measurements for large areas resulting in significant reduction of costs. The main stakeholders at heights data received from the airborne laser scanning is mainly state administration. The state institutions appear among projects such as ISOK. Each point is classified in accordance with the standard LAS 1.2, our research focuses on the class 6 – buildings. In the project ISOK, the buildings are not measured in whole (from every side). A typical way to measure the missing elements is to increase the coverage of the cross and additional raids which unfortunately increases the cost measurements. An alternative solution density point clouds ALS is the use of optical scanning and UAV. The article shows the process of density the point clouds coming from ALS using point cloud obtained through optical scanning. The methods that illustrate the process of compaction data format LAS using the following methods: point cloud having field coordinates in the system compatible with the system of clouds acquired with ALS, point cloud in the local system, point cloud in the local system without the scale. The file size, depending on the density of the point cloud was analyzed.